COVID-19 and the Structural Crises of Our Time - Mah-Hui, Lim (Book collections on Project MUSE., 2021)
""We live in paradoxical times. Traditionally, the West has led the world in theory and practice. Yet, recent developments, from COVID-19 to the storming of the US Capitol, show how lost the West has become. This loss of direction has deep roots. In their usual thoughtful and incisive fashion, Lim Mah-Hui and Michael Heng Siam-Heng, draw out the deeper origins of our current crises and show us a new way forward. A must-read for anyone who wants to understand our strange times."" -- Kishore Mahbubani, founding Dean of the Lee Kuan Yew School of Public Policy, National University of Singapore, i.